Information About Khiva Madrasas is Reflected in the Works of Local Historians - Sultanovich, Yusupov Hamidbek (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the reflection of Khiva madrasas in written sources is studied for the first time. Among them, the scientific heritage of historians such as Shermuhammad Munis, Muhammadrizo Ogahi, Muhammad Yusuf Bayani, Hasanmurad Laffasi, Syed Hamid Tora Komyob, Bobojon Tarroh, Mirzo Olim Makhdum Haji, who lived and personally witnessed the economic, social, political and cultural processes that took place during the Khiva Khanate period, is important. Takes place. It should be noted that these historians, in addition to highlighting important historical details, also expressed personal opinions in their works. In this period, the Khiva khanate’s reign of the Kungirot dynasty is particularly noteworthy. Along with all fronts, the country entered history with the development of its cultural life. In this period, the construction of madrasahs and their architecture, management, material support, educational process, libraries and activities of teachers are noteworthy.